The Relationship of Menstrual Hygiene Behavior with Menstrual Cycle Disorders in Female Prisoners: A Sequential Explanatory Analysis - Sari, Nur Purnama; Utama, Bobby Indra; Amir, Arni (Newinera Publisher, 2024)
Menstrual hygiene behaviors, such as using clean sanitary napkins, washing the body with soap, and disposing of used sanitary napkins properly, play an important role in preventing menstrual disorders. This quantitative study aims to examine the relationship between menstrual hygiene behavior and menstrual cycle disorders in female prisoners in class II B women's prison in Padang city. Qualitative research aims to explore more deeply the behavior of inmates who experience menstrual cycle disorders in class II B women's prison in Padang city. This research used a combination method with a sequential explanatory design from November 2023 to March 2024, the research sample consisted of 73 female prisoners selected by purposive sampling. Quantitative data analysis using the chi-square test showed a significant association (p-value <0.001) between menstrual hygiene behavior and menstrual cycle disorders, while qualitative data through in-depth interviews identified two main themes: menstrual hygiene behavior and menstrual cycle disorders. In conclusion, poor menstrual hygiene behavior is associated with menstrual cycle disorders, so it is recommended that prison authorities increase supervision and provide better information on menstrual hygiene to prisoners.